Relationship between Pollutant Sources and Water Quality of Dug Well Based on Biological Parameters of E. Coli - Deni Rusmaya; Lili Mulyatna; Putri Ayu Lestari (Journal of Community Based Environmental Engineering and Management, 2022)
Water from dug wells is one of the sources of clean water used by the community both in villages and cities. Groundwater consumed by the community must have quality in accordance with the specified requirements. One of the important parameters is the presence of Escherichia coli bacteria (E.coli). The aims of this study is to identify the presence of Escherichia coli bacteria in dug well. In addition, to determine the correlation between the distance of the pollutant source (cowshed and septic tank) and the well. The analytical method used is univariate descriptive method and quantitative analysis. The results showed from 7 wells that were used as research objects, there were 4 wells positive for E. Coli bacteria and 3 wells were negative for E. Coli bacteria. The correlation value test showed that the pollutant source from cowshed had a coefficient of determination of R 2 = 0.911 or 91.1% which means that there is a strong relationship between the presence of E.Coli bacteria in the well and cow dung. As for the pollutant source from the septic tank, the results of the correlation test show the value of R 2 = 0.201 or 20.1% which means that the relationship between the presence of E. Coli bacteria and the septic tank is not strong. Septic tanks construction that conform to standards are one of the factors that cause dug well water quality to remain protected from pollutants.